2017
DOI: 10.1016/j.eplepsyres.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of perampanel in lithium-pilocarpine rat seizure model

Abstract: PER exhibited a strong neuroprotective effect in a drug-refractory SE model, and this effect was correlated with its attenuation of seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Perampanel is also approved for monotherapy use for focal seizures in the United States. 18 To our knowledge, this has not been demonstrated in humans with SE. 18 To our knowledge, this has not been demonstrated in humans with SE.…”
Section: Intermsoftheunderlyingpathophysiologysemightarisefrommentioning
confidence: 78%
See 4 more Smart Citations
“…Perampanel is also approved for monotherapy use for focal seizures in the United States. 18 To our knowledge, this has not been demonstrated in humans with SE. 18 To our knowledge, this has not been demonstrated in humans with SE.…”
Section: Intermsoftheunderlyingpathophysiologysemightarisefrommentioning
confidence: 78%
“…8,15 InEurope,perampanel,aselective,non-competitiveAMPAreceptor antagonist, is indicated as an adjunctive treatment for focal seizures, with or without secondarily generalized seizures, in pa-tientsaged≥12years,andfortheadjunctivetreatmentofprimary generalized tonic-clonic seizures in patients with idiopathic generalized epilepsy aged ≥12years. Studies in the rat lithium-pilocarpine model of SE have suggested that perampanel may have efficacy in terminating prolonged seizures 17,18 while providing neuroprotection, though the level of neuroprotective effects varied by region. Studies in the rat lithium-pilocarpine model of SE have suggested that perampanel may have efficacy in terminating prolonged seizures 17,18 while providing neuroprotection, though the level of neuroprotective effects varied by region.…”
Section: Intermsoftheunderlyingpathophysiologysemightarisefrommentioning
confidence: 99%
See 3 more Smart Citations